Reflections on Informatic Crime in the Republic of Moldova - Andrei NASTAS; Sergiu CERNOMOREȚ; Anatolie FAIGHER (ACROSS)
The evolution of the socio-economic sphere inevitably generates changes in the criminal phenomenon, in this sense, the Republic of Moldova is not an exception. In recent years, there has been a growing spread of cybercrime. In addition, a number of crimes involve the increasing use of information technology in crime.